(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A Scholarship in the real sense of the word isfinancial aid given to a student because of academic merit with the purpose ofencouraging such students in their academic pursuits. A number of scholarshipschemes are sponsored by the Government of India without losing sight of themain purpose i.e. giving financial aid on the basis of merit. The Government ofIndia judiciously recognizes the financial burden entailed on parents/guardiansbelonging to Scheduled Castes and Scheduled Tribe, who desire that theirchildren/Wards continue and complete their education so as to ensure theirfuture jobs and realization of their aspired careers. For this purposePost-matric Scholarship Schemes for students belonging to Scheduled Castes andScheduled Tribes are provided accordingly. Recognizing the fact thateducational avenues are many and varied, scholarship schemes also cover suchstudents who opt for full-time educational courses through Distant Educationmode or through Correspondence Courses.